Anterior cruciate ligament injuries in female athletes, Part 1, Mechanisms and risk factors - Hewett, T. E.; Ford, K. R.; Myer, G. D. (The American Journal of Sports Medicine, 2006)
The mechanism underlying gender disparity in anterior cruciate ligament injury risk is likely multifactorial in nature. Several theories have been proposed to explain the mechanisms underlying the gender difference in anterior cruciate ligament injury rates. These theories include the intrinsic variables of anatomical, hormonal, neuromuscular, and biomechanical differences between genders and extrinsic variables. Identification of both extrinsic and intrinsic risk factors associated with the anterior cruciate ligament injury mechanism may provide direction for targeted prophylactic treatment to high-risk individuals